Determination of an Optimal Oil Jet Nozzle Layout for Helical Gear Lubrication: Mathematical Modeling, Numerical Simulation, and Experimental Validation - Yu Dai; Jifu Jia; Bin Ouyang; Jianeng Bian (Complexity)
To provide a basic guidance for the selection of nozzle layout, a mathematical model of the impingement depth for helical gears under oil jet lubrication is established. Furthermore, computational fluid dynamics (CFD) methods are adopted to validate the effectiveness and accuracy of the derived impingement model. Firstly, the distribution characteristics of the oil volume fraction and oil-gas pressure in meshing area were obtained in flow field simulation. Meanwhile, the influence of spray angle, jet velocity, and gear ratio on lubrication effect was obtained. Then, the transient temperature field of the tooth surface was simulated by the method of thermal-fluid coupling analysis, and the lowest temperature distribution and the corresponding oil jet velocity were determined. Finally, experiments on the temperature characteristics measured by an infrared thermal imager of helical gears with different nozzle parameters were carried out in a gear test rig. The simulation results of transient temperature field are in good agreement with those obtained by experiments, and it indicates that the thermal-fluid coupling analysis method is correct and feasible to predict the temperature field of the helical gear pair under oil injection jet lubrication.